Posttraumatic thoracic splenosis in a 77-year-old patient after a motor vehicle accident - Suzanne Maddamma; Kwabena G. Owusu-Ansah; Timothy Barreiro (Respiratory Medicine Case Reports, 2023)
We present a rare case of autotransplantation of splenic tissue to the thoracic cavity, concerning for lung tumor, after splenic and diaphragmatic injury following a severe motor vehicle accident 27 years previous.